Anti-Lymphoma Efficacy Comparison of Anti-Cd20 Monoclonal Antibody-Targeted and Non-Targeted Star-Shaped Polymer-Prodrug Conjugates - Lidický, Ondřej; Janoušková, Olga; Strohalm, Jiří; Alam, Mahmudul; Klener, Pavel; Etrych, Tomáš (Molecules (Basel, Switzerland), 2015)
Here we describe the synthesis and biological properties of two types of star-shaped polymer-doxorubicin conjugates: non-targeted conjugate prepared as long-circulating high-molecular-weight (HMW) polymer prodrugs with a dendrimer core and a targeted conjugate with the anti-CD20 monoclonal antibody (mAb) rituximab (RTX). The copolymers were linked to the dendrimer core or to the reduced mAb via one-point attachment forming a star-shaped structure with a central antibody or dendrimer surrounded by hydrophilic polymer chains. The anticancer drug doxorubicin (DOX) was attached to the N-(2-hydroxypropyl)methacrylamide (HPMA)-based copolymer chain in star polymer systems via a pH-labile hydrazone linkage. Such polymer-DOX conjugates were fairly stable in aqueous solutions at pH 7.4, and the drug was readily released in mildly acidic environments at pH 5-5.5 by hydrolysis of the hydrazone bonds. The cytotoxicity of the polymer conjugates was tested on several CD20-positive or negative human cell lines. Similar levels of in vitro cytotoxicity were observed for all tested polymer conjugates regardless of type or structure. In vivo experiments using primary cell-based murine xenograft models of human diffuse large B-cell lymphoma confirmed the superior anti-lymphoma efficacy of the polymer-bound DOX conjugate when compared with the original drug. Targeting with RTX did not further enhance the anti-lymphoma efficacy relative to the non-targeted star polymer conjugate. Two mechanisms could play roles in these findings: changes in the binding ability to the CD-20 receptor and a significant loss of the immunological properties of RTX in the polymer conjugates.
Keywords: apoptóza; doxorubicin; Rituximab; lidé; Xenograft Model Antitumor Assays; Apoptosis; prekurzory léčiv; Lymphoma; Cell Line, Tumor; Prodrugs; Antineoplastic Agents; Doxorubicin; Drug Liberation; Cell Survival; protinádorové látky; monoclonal antibody; lékové transportní systémy; myši; Drug Delivery Systems; Humans; lymfom; Mice; uvolňování léčiv; Disease Models, Animal; viabilita buněk; Polymers; rituximab; zvířata; polymery; drug targeting; Animals; xenogenní modely - testy protinádorové aktivity; nádorové buněčné linie; HPMA copolymers; modely nemocí na zvířatech; drug delivery systems